Current limitations and perspectives of chimeric antigen receptor-t-cells in acute myeloid leukemia - Maucher, Marius; Srour, Micha; Danhof, Sophia; Einsele, Hermann; Hudecek, Michael; Yakoub-Agha, Ibrahim (Cancers, 2021)
Adoptive transfer of gene-engineered chimeric antigen receptor (CAR)-T-cells has emerged as a powerful immunotherapy for combating hematologic cancers. Several target antigens that are prevalently expressed on AML cells have undergone evaluation in preclinical CAR-T-cell testing. Attributes of an ‘ideal’ target antigen for CAR-T-cell therapy in AML include high-level expression on leukemic blasts and leukemic stem cells (LSCs), and absence on healthy tissues, normal hematopoietic stem and progenitor cells (HSPCs). In contrast to other blood cancer types, where CAR-T therapies are being similarly studied, only a rather small number of AML patients has received CAR-T-cell treatment in clinical trials, resulting in limited clinical experience for this therapeutic approach in AML. For curative AML treatment, abrogation of bulk blasts and LSCs is mandatory with the need for hematopoietic recovery after CAR-T administration. Herein, we provide a critical review of the current pipeline of candidate target antigens and corresponding CAR-T-cell products in AML, assess challenges for clinical translation and implementation in routine clinical practice, as well as perspectives for overcoming them.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Adoptive cell therapy; AML; CAR-T-cell; Gene therapy; Hematology